Digitizing Waste Management Using the Internet of Things: Research Opportunities - Windi Auliana; Q. Qurtubi; H. Haswika; Kongkidakhon Worasan; Mohammad A. Shbool (Universitas Ahmad Dahlan, 2026)
This study proposes an integrative multi-layered framework to address fragmentation in industrial waste management. The increasing volume of industrial waste creates an urgent need for a more precise, adaptive, and sustainable control system, as current practices often lack sufficient integration to ensure full environmental accountability. A critical gap exists in the lack of integration between real-time technical data and strategic governance, which hinders